Analisis Kelayakan Usaha Budidaya Udang Vaname (Litopenaeus vannamei) Sistem Intensif (Studi Kasus : Usaha Tambak Pak Boy Kabupaten Aceh Tamiang) - Mukhlis Maulana; Rozalina Rozalina; Silvia Anzitha (Program Studi Agribisnis Fakultas Pertanian Universitas Samudra, 2022)
This study aims to determine the investment costs, total production costs and income for the intensive system of Vannamei shrimp (Litopenaeus vannamei) and to determine the feasibility study of the intensive system of Vannamei shrimp (Litopenaeus vannamei) cultivation (Case Study: Pak Boy Pond Business in Seruway District). Aceh Tamiang Regency) seen from the Break Even Point (BEP), Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C Ratio), Payback Period (PP) and Internal Rate of Return (IRR).This research is a case study research and was carried out on an intensive system of vaname shrimp cultivation at Pak Boy Pond Business located in Seruway District, Aceh Tamiang Regency. The sampling technique for this research was done intentionally (purposive sampling). Purposive sampling is a sampling technique or data source with certain considerations, namely people who really understand the conditions of Pak Boy's Pond Business. The subject of this research as a resource person is Mr. Boy as the owner of the business. There are two methods of data analysis used to determine the feasibility of this intensive system of vaname shrimp farming, namely income analysis and business feasibility analysis. The research results obtained are; 1) The investment cost of Pak Boy's Pond Business is Rp. 3.216.800.000,-. The total cost of production in one year is Rp. 4,589,387,000,-. Total income in one year is Rp. 5.289.922.000,-. 2) Production BEP is 75,889 Kg and the production of Pak Boy Pond Business exceeds the BEP value of production which is 134,592 Kg, BEP price is Rp. 34,099.00 and the average selling price of vaname shrimp exceeds the BEP Price of Rp. 60,475.00, Ratio Net B/C obtained is 6.9 greater than 1, Payback period is 0.6 years, NPV obtained is 19,066,275,861 greater than 0, IRR obtained is 163.14% greater than the stated interest rate . So it can be said that the intensive system of vaname shrimp cultivation in Pak Boy's Pond is feasible.